Response of Mixed-Phase Cloud Microphysical Properties to Cloud-Seeding Near Cloud Top Over Hebei, China - Yang, Yang; Zhao, Chuanfeng; Fu, Jiao; Cui, Yi; Dong, Xiaobo; Mai, Rong; Xu, Feng (Frontiers in Environmental Science, 2022)
On November 29, 2019, an aircraft observation during the period of cloud-seeding was carried out for a mixed-phase cloud over Xingtai, Hebei province, China. This study investigates the response of mixed-phase cloud microphysical properties to cloud-seeding near cloud top. Before cloud seeding, the cloud droplet concentration from FCDP (NC_FCDP) presented a multi-peak vertical distribution structure, with a maximum concentration of 192cm-3 at the height of 3322 m; the maximum concentration of ice crystals from CIP (NC_CIP) was 10L-1 which appeared at 4500 m in the upper part of cloud; and the peak value of liquid water content (LWC) in the cloud also appeared at 4500 m with a value of 0.15 g/m3. The coexistence of supercooled liquid water and ice crystals implies that they are particularly suitable for cloud seeding at the height of 4550 m. About 7-8 minutes later after cloud seeding at this height, the average NC_FCDP decreased from 160.3 cm-3 to 129 cm-3, and the average NC_CIP increased from 7.1 L-1 to 10 L-1. Moreover, after cloud seeding, high NC_CIP, as well as larger and more ice crystals appeared almost in the same areas within the cloud, and LWC presented an obvious decreasing trend. In contrast, the concentration of small cloud droplets and LWC decreased obviously after seeding. The findings suggest that the cloud microphysical properties showed obvious responses to artificial introduction of silver iodide, which is important for human weather modification.